Wschód contra Zachód. Komplementarne opozycje w procesie percepcji poematu Wieniedikta Jerofiejewa pt. Moskwa-Pietuszki - Waligorska-Olejniczak, Beata (Instytut Filologii Słowiańskiej, 2012)
The focus of the analysis is the issue of complementary oppositions functioning in the perception of Moskva-Petushki by Venedict Erofeev. The tool utilised in this process appears to be Sergei Eisenstein's theory of ecstasy, which turns our attention to the problem of montage of literary frames, the length of scenes and the emotional atmosphere of the discussed work of art. The studies focused on these parametres allow us to discover the pulsating dynamics of binary oppositions existing in the structure of the poem, among which the key issue is the dialogue of the mentality of the East and the West. The collage reality of Venichka becomes also the subject of the discussion related to the identity of the human being today and the role of culture as the medium revealing the change of the relationship between sacrum and profanum. The change motivates the reader to consider the problem of stereotype thinking, which today constitutes one of the most relevant issues.
East contra West. Complementary Oppositions in the Process of Perception of Moscow-Petushki- by Venedict Erofeev
Keywords: Jerofiejew; Erofeev; Eisenstein; montaż; montage; Moskwa-Pietuszki; Moscow-Petushki